The Potential of Halal Tourism for Regional Economy and Community Income: Evidence from South Kalimantan - Syaugi Syaugi; Yusuf Asyahri; Faqih El Wafa (Islamiconomic : Jurnal Ekonomi Islam, 2025)
The purpose of this study is to analyze the potential of halal tourism for the regional economy and its impact on community income in South Kalimantan. This study employs a combination of qualitative and quantitative approaches. The sampling technique employed was cluster sampling in three districts/cities, with a sample size of 100 respondents determined through quota sampling. The data collection technique used was structured interviews, followed by triangulation to validate the interview results. Data analysis was conducted using the Miles and Huberman approach to identify the potential for halal tourism, while quantitative analysis employed the multiplier effect approach to measure the economic impact. The study's results demonstrate the potential of halal tourism in South Kalimantan, highlighting its appeal through river destinations, floating markets, religious sites, natural attractions, marine activities, culture, and cuisine. The Keynesian Local Income Multiplier value is 1.09. Meanwhile, the Type I Income Multiplier Ratio is 3.63 and Type II is 4.15, indicating a significant increase in the income of business owners, workers, and local consumption. This study contributes to the Islamic economic literature by providing halal tourism development that not only supports regional economic growth but also aligns with Sharia principles to create mutual benefits.